2013
DOI: 10.1021/es305293h
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Effects of Biochar on Manure Composting: Evidence Supporting the Relationship between N2O Emission and Denitrifying Community

Abstract: Although nitrous oxide (N2O) emissions from composting contribute to the accelerated greenhouse effect, it is difficult to implement practical methods to mitigate these emissions. In this study, the effects of biochar amendment during pig manure composting were investigated to evaluate the inter-relationships between N2O emission and the abundance of denitrifying bacteria. Analytical results from two pilot composting treatments with (PWSB, pig manure + wood chips + sawdust + biochar) or without (PWS, pig manur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
88
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(101 citation statements)
references
References 39 publications
7
88
1
Order By: Relevance
“…In these composts, concentrations of denitrifiers were similar in FT and ST composts and there were no significant differences in concentrations between samples regardless of turning frequency, compost time or season (Table 5). This is in contrast to findings of Angnes et al (2013) and Wang et al (2013) which showed that concentrations of genes for denitrification (i.e., norB, nosZ, nirK and nirS) varied over the course of composting and that the concentrations were correlated with N 2 O emissions in swine slurry composts. These HRFF materials had been accumulated/ stored and partially decomposed while under the high-rise facilities for two to three months prior to composting, likely permitting accumulation of denitrifiers and accounting for higher concentrations in the initial compost materials.…”
Section: Microbiological Analysis Of Nitrifiers and Denitrifierscontrasting
confidence: 99%
See 2 more Smart Citations
“…In these composts, concentrations of denitrifiers were similar in FT and ST composts and there were no significant differences in concentrations between samples regardless of turning frequency, compost time or season (Table 5). This is in contrast to findings of Angnes et al (2013) and Wang et al (2013) which showed that concentrations of genes for denitrification (i.e., norB, nosZ, nirK and nirS) varied over the course of composting and that the concentrations were correlated with N 2 O emissions in swine slurry composts. These HRFF materials had been accumulated/ stored and partially decomposed while under the high-rise facilities for two to three months prior to composting, likely permitting accumulation of denitrifiers and accounting for higher concentrations in the initial compost materials.…”
Section: Microbiological Analysis Of Nitrifiers and Denitrifierscontrasting
confidence: 99%
“…Similar criteria are necessary for amendments in HRFF; in this case woodchips were dry, maintained structure while under the production facility, and the size (average 1.9 ± 0.9 cm) was highly variable making them adequate for both liquid absorption and as bulking agent to supply structure and improve aeration. Initial nutrient levels and C/N ratios of the slurry-woodchip mix used in this study were similar to those of other swine waste composts (Tables 1 and 2; Bustamante et al, 2013;Tiquia et al, 2002;Wang et al, 2013) although initial C/N ratio and moisture content were lower than similar products from other HRFF (Table 1; Keener et al, 2001;Stowell, 2002). The initial swine slurry-woodchip mix obtained for the FT and ST differed significantly in terms of pH, N, ammonium (NH 4 + ), phosphorous (P), potassium (K), moisture and C/N ratio (P < 0.10); likely due to differences in the amount of time the material was maintained under the finishing facility, the amount of bulking material added, frequency of turning and/or seasonal conditions (temperature, moisture, humidity).…”
Section: Initial High-rise Slurry-woodchip MIX Characteristicssupporting
confidence: 75%
See 1 more Smart Citation
“…S3(e)): nosZ gene clade II was 2.8-fold more abundant on day 131 than on day 228, indicating that higher abundances of N 2 O-reducing bacteria facilitated N 2 O consumption in the anoxic tank. The degree and relative rate of N 2 O consumption are potentially reflected in the abundance ratio of nosZ/(nirK+nirS) (Wang et al 2013). The abundance ratios of the genes are presented in Fig.…”
Section: Microbial Community Analysesmentioning
confidence: 99%
“…Limited literature indicated that (1) biochar can be used as a bulking agent. The aeration and structure of compost materials may be improved due to the high porosity and low density of the biochar (Sonoki et al 2011); (2) biochar can hold moisture due to its large porosity and high water holding capacity (Wang et al 2013). Appropriate moisture content is critical to composting; (3) due to its large surface and porosity, biochar may alter and retain microorganisms in composting (Zhang et al 2014).…”
Section: Introductionmentioning
confidence: 99%